Heidi Heckelbeck and the big mix-up - Coven, Wanda (Coven, Wanda. Heidi Heckelbeck, 2016)
Heidi learns that words can hurt when an embarrasing rumor about Lucy spreads at school. What's worse is that Lucy thinks Bruce is behind it-- and she's ready to spill one of his secrets for revenge. Stuck between her two best friends, can Heidi find a way to bring everyone back together before the trio splits up forever?